2021
DOI: 10.3390/polym14010158
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of Large-Scale Hollow Section RC Beams and Strength Enhancement Using Carbon Fiber Reinforced Polymer (CFRP) Composites

Abstract: An experimental program was conducted to ascertain the efficiency of Carbon Fiber Reinforced Polymer (CFRP) in enhancing the flexural response of hollow section reinforced concrete (RC) beams. Nine beams were tested under four-point bending in three groups. Beams were categorized to reflect the presence or configuration of the CFRP sheet. Each group consisted of three beams: one with a solid section, one with a square 50×50  mm × mm opening and 1 with 100×100  mm × mm opening. Beams in 1st group were tested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Based on the convergence study, a 20 mm sized mesh was utilized, and a fine mesh of 10 mm was used near the notch section. All material properties in the CDP model for the M40-grade concrete were adapted from [14,59]. The mechanical properties for the M40-grade concrete are given in Table 5, and Table 6 shows the mechanical properties of the repairing materials.…”
Section: Present Numerical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the convergence study, a 20 mm sized mesh was utilized, and a fine mesh of 10 mm was used near the notch section. All material properties in the CDP model for the M40-grade concrete were adapted from [14,59]. The mechanical properties for the M40-grade concrete are given in Table 5, and Table 6 shows the mechanical properties of the repairing materials.…”
Section: Present Numerical Studymentioning
confidence: 99%
“…It was found that, as the size of the web opening increased, the shear strength of the concrete deep beam decreased. As discussed in Figure 1, various techniques can be used, like jacketing [11,12] and FRP [13,14]. Researchers generally investigate the performance of any repair and strengthening technique, as discussed above, by imitating damages, defects and cracks in the concrete beam through embedding a notch approximately in the middle of the beam.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively new for reinforcement in the calculation of building structures is high-strength non-metallic reinforcement made of composite materials [ 41 , 42 , 43 , 44 , 45 , 46 ]. Polymer composite reinforcement is mainly produced in the form of a rod with a spiral relief of any construction length made of glass or basalt fibers impregnated with a chemically resistant polymer [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mineral impregnated carbon fiber composites are a new type of reinforcement for construction. Compared to steel reinforcement, carbon fiber reinforcement has a much higher tensile strength and a significantly lower weight [ 22 , 24 , 31 , 33 , 35 , 38 , 39 , 41 , 42 , 43 , 44 , 47 , 49 , 51 , 55 , 59 ]. At present, the technology of reinforcing concrete bending elements with carbon fiber sheets is popular [ 44 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, fiber composites are the most widely used and developed materials. The most recently used fiber-reinforcing agent is carbon fiber (CF), which is mixed with various matrix materials [1][2][3][4][5][6][7][8]. However, these carbon fibers are expensive and have disadvantages.…”
Section: Introductionmentioning
confidence: 99%